2015
DOI: 10.4238/2015.december.29.39
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNPs in the PPARγ gene and hypertension in a Mongolian population

Abstract: ABSTRACT. The association of single nucleotide polymorphisms (SNPs) in PPARγ with hypertension is controversial. The aim of the present study was to clarify the contributions of PPARγ genetic variants to hypertension through an association study. A total of 414 unrelated Mongolian herdsmen and 524 Han farmers were included in this study. Fourteen intronic SNPs were analyzed and genotyped using a polymerase chain reaction/ligase detection reaction assay. Prior to correction for multiple testing, the SNPs rs68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…으로 알려져 있는데 [7][8][9], 그 중에서 MACROD2 (MACRO domain containing 2) 유전자가 심혈관 질환 및 고혈압과 상관 관계가 있는 것으로 발표되었다 [10][11][12][13]. MACROD2는 mono-ADP-ribosylated 된 단백질로부터 ADP-ribose를 제거하는 데 관여하는 탈아세틸화효소의 기능을 가지고 있는데, DNA 손 상 시 핵에서 세포질로 전위하는 것으로 나타났으며, 이는 태아 와 성인의 뇌, 흉선, 골격근, 간, 췌장, 전립선, 신장, 폐에서 발현 하며 쥐 배아와 성체의 in situ hybridization과 RT-PCR분석에 서 배아일 12.5일에서 성년기까지 두뇌, 특히 심실영역에서의 발현을 나타냈다 [14].…”
unclassified
“…으로 알려져 있는데 [7][8][9], 그 중에서 MACROD2 (MACRO domain containing 2) 유전자가 심혈관 질환 및 고혈압과 상관 관계가 있는 것으로 발표되었다 [10][11][12][13]. MACROD2는 mono-ADP-ribosylated 된 단백질로부터 ADP-ribose를 제거하는 데 관여하는 탈아세틸화효소의 기능을 가지고 있는데, DNA 손 상 시 핵에서 세포질로 전위하는 것으로 나타났으며, 이는 태아 와 성인의 뇌, 흉선, 골격근, 간, 췌장, 전립선, 신장, 폐에서 발현 하며 쥐 배아와 성체의 in situ hybridization과 RT-PCR분석에 서 배아일 12.5일에서 성년기까지 두뇌, 특히 심실영역에서의 발현을 나타냈다 [14].…”
unclassified
“…Peroxisome proliferator-activated receptor γ (PPARγ) is mainly located in the basal ganglia and other places where dopamine receptors are expressed, indicating a possible correlation between PD and PPARγ [2,3]. PPARγ is a member of the steroid hormone receptor superfamily and a ligand-activated transcriptional factor [4]. In the last few years, animal model studies have shown an association between PPARγ and PD with a series of experiments demonstrating that PPARγ agonists could protect neurons from injury [2,5].…”
Section: Introductionmentioning
confidence: 99%